2016
DOI: 10.1093/ajcp/aqv083
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of ELISA and Chemiluminescent Assays as Alternative Screening Tests to Indirect Immunofluorescence for the Detection of Antibodies to Cellular Antigens

Abstract: Some ELISA kits have comparable or superior diagnostic sensitivity to ANA HEp-2 and could be used as an alternative method for ANA screening, therefore allowing the immediate report of the results with fewer false negatives than ANA HEp-2. Owing to the lower specificity, ELISA-positive samples should be submitted to ANA HEp-2 for confirmation of results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The HSROC plot of the study estimates for ELISA sensitivity vs. specificity is similar to IIF: variance in the test results across the studies lead to a high level of uncertainty in the estimates of diagnostic test accuracy (a large prediction region). Figure 1, top right panel, shows 10 ELISA test results (from six studies [43,[45][46][47][48]54]) with a similar association between increased sensitivity and decreased specificity as IIF. A HSROC plot of ELISA test data for ELISAs with and without a HEp-2 component is shown in Supplementary Material, Figure S-2.…”
Section: Summary Of Study Estimates Of Diagnostic Accuracy By Testmentioning
confidence: 84%
See 3 more Smart Citations
“…The HSROC plot of the study estimates for ELISA sensitivity vs. specificity is similar to IIF: variance in the test results across the studies lead to a high level of uncertainty in the estimates of diagnostic test accuracy (a large prediction region). Figure 1, top right panel, shows 10 ELISA test results (from six studies [43,[45][46][47][48]54]) with a similar association between increased sensitivity and decreased specificity as IIF. A HSROC plot of ELISA test data for ELISAs with and without a HEp-2 component is shown in Supplementary Material, Figure S-2.…”
Section: Summary Of Study Estimates Of Diagnostic Accuracy By Testmentioning
confidence: 84%
“…The literature review (up to March 2018) identified 17 studies (from 18 citations [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]) that met the inclusion criteria for this review (set out in the section Inclusion criteria) (see PRISMA diagram in Supplementary Material, Figure S-1). A summary of the studies is provided in Table S…”
Section: Summary Of Studies Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, these tests require a high sensitivity and specificity to prevent false positives and false negatives. The enzyme-linked immunosorbent assay (ELISA) provides a familiar example, as it represents the mainstay of analytical biochemistry and may also replace indirect immunofluorescence for the detection of autoantibodies [43]. ELISAs are used as both a diagnostic tool and an assay for the purpose of discerning the concentration of analytes, particularly proteins within a solution of proteins [44].…”
Section: Diagnostic Applications For Aptamersmentioning
confidence: 99%